Surface Roughness and Color Stability of Conventional and Bulk-Fill Resin Composite with S-PRG Fillers After Coffee Exposure: An in-vitro Study - Janisch FADS; Falcon Aguilar M; Aguiar FHB; França FMG; Basting RT; Vieira-Junior WF (Clinical, Cosmetic and Investigational Dentistry)
Fabiano Augusto Dos Santos Janisch,1 Milagros Falcon Aguilar,2 Flávio Henrique Baggio Aguiar,2 Fabiana Mantovani Gomes França,1 Roberta Tarkany Basting,1 Waldemir Francisco Vieira-Junior2 1Department of Restorative Dentistry, Faculdade São Leopoldo Mandic, Campinas, SP, Brazil; 2Department of Restorative Dentistry, Faculdade de Odontologia de Piracicaba, Universidade Estadual de Campinas, Piracicaba, SP, BrazilCorrespondence: Waldemir Francisco Vieira-Junior, Faculdade de Odontologia de Piracicaba, Universidade, Estadual de Campinas, Av. Limeira, 901 – Areião, Piracicaba, SP, Brazil, Tel +55 (19) 21065220, Email waljr@unicamp.brObjective: This study aimed to evaluate the in vitro effects of coffee exposure on the color and roughness of conventional and bulk-fill resin composites, with and without surface pre-reacted glass-ionomer (S-PRG) filler.Methodology: Forty-eight cylindrical samples (Ø 6 mm × 2 mm) were prepared and categorized as follows (n = 12 per group): conventional nano-hybrid (Tetric N-Ceram, Ivoclar); nano-hybrid with S-PRG filler (Beautifil II, Shofu); bulk-fill (Tetric N-Ceram Bulk Fill, Ivoclar); and bulk-fill with S-PRG filler (Beautifil Bulk Restorative, Shofu). The samples were assessed for surface roughness (Ra, μm), color coordinates (CIE Lab), and overall color change (ΔEab, ΔE00). Measurements were taken at baseline and after 7 days of coffee immersion (pH = 4.95). Data were analyzed using generalized linear models, Kruskal–Wallis, Dunn, and paired Wilcoxon tests (α = 0.05).Results: After the coffee exposure, all resin composites exhibited a significant decrease in L* (towards black), an increase in a* (towards red), an increase in b* (towards yellow), and a higher Vita color score (p < 0.05). Tetric N-Ceram demonstrated the lowest roughness values post-exposure; however, a significant increase in roughness over time was observed only for Tetric N-Ceram Bulk Fill (p < 0.05). For ΔEab, Beautifil Bulk Restorative and Tetric N-Ceram showed higher values compared to Beautifil II. For ΔE00, a significant difference was noted between Beautifil Bulk Restorative and Beautifil II (p < 0.05).Conclusion: Resin composites with S-PRG fillers exhibited similar pigmentation dynamics to conventional composite but showed greater surface roughness after exposure to coffee. Considering the S-PRG materials, the bulk-fill version is more susceptible to staining.Keywords: composite resins, coffee, color, surface properties